The interplay between emotional intelligence, oral communication skills and second language speaking anxiety: a structural equation modeling approach - Ali Alghorbany,; Mohd Hilmi Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study aimed at identifying the association between Goleman’s emotional intelligence and second language speaking anxiety by employing oral communication skills as the mediating variable. A correlational research design was used. A total of 209 first and second-year Malaysian undergraduate ESL students were selected from one public university in Malaysia. The study employed the proportionate stratified random sampling. In order to collect data, three questionnaires including ‘Emotional Competence Inventory (ECI)’, ‘Foreign Language Classroom Anxiety Scale (FLCAS)’, and ‘Oral Communication Skills Scale’ were used. Testing the hypotheses required correlational analysis done via Smart PLS 3.0. Results provided support for the proposed conceptual framework, disclosing that emotional intelligence was significantly associated with oral communication skills. Also, oral communication skills were significantly associated with second language speaking anxiety. Lastly, oral communication skills mediated the association between emotional intelligence and second language speaking anxiety. The current study offered ESL students, educator and policymakers several theoretical and practical implications.